Sensitive ligand-based protein quantification using immuno-PCR: A critical review of single-probe and proximity ligation assays. (May 2014) - Hansen, Marcus Celik; Nederby, Line; Henriksen, Mads Okkels-Birk; Hansen, Maria; Nyvold, Charlotte Guldborg
Quantitative PCR (qPCR) of reverse-transcribed mRNA has revolutionized gene expression analyses. qPCR analysis is based on the prevalent assumption that mRNA transcript numbers provide an adequate measure of specific biomarker expression. However, taking the complexity of protein turnover into account, there is a need to correlate qPCR-derived transcriptional patterns with protein translational patterns so as to not leave behind important pathobiological details. One emerging approach in protein analysis is PCR-coupled protein quantification, often denoted as immuno-PCR (iPCR), which targets soluble proteins. Here we review recent trends and applications in iPCR assays that may bridge the gap between classical enzyme-linked immunosorbent assays and mass spectrometry methodologies in terms of sensitivity and multiplexing.